2021
DOI: 10.3389/fphar.2021.639716
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Advanced Multicellular Intestinal Model for Assessing Immunomodulatory Properties of Anti-Inflammatory Compounds

Abstract: Intestinal inflammation is the collective term for immune system-mediated diseases of unknown, multifactorial etiology, with often complex interactions between genetic and environmental factors. To mechanistically investigate the effect of treatment with compounds possessing immunomodulating properties in the context of intestinal inflammation, we developed an immunocompetent in vitro triculture intestinal model consisting of a differentiated intestinal epithelial layer (Caco-2/HT29-MTX) and immunocompetent ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…In addition, nicotine was further shown to improve intestinal inflammation by inhibiting the stimulation of IFN-g, TNF-a, and IL-1b in intestinal epithelial cell CaCO-2 cocultured with enteric glial cells (41). However, a similar effect was not found in the triculture intestinal model consisting of a differentiated intestinal epithelial layer (CaCO-2/ HT29-MTX) and immunocompetent cells (differentiated THP-1) (42).…”
Section: Anti-inflammatory Effect Of Nicotine On Ibdmentioning
confidence: 75%
“…In addition, nicotine was further shown to improve intestinal inflammation by inhibiting the stimulation of IFN-g, TNF-a, and IL-1b in intestinal epithelial cell CaCO-2 cocultured with enteric glial cells (41). However, a similar effect was not found in the triculture intestinal model consisting of a differentiated intestinal epithelial layer (CaCO-2/ HT29-MTX) and immunocompetent cells (differentiated THP-1) (42).…”
Section: Anti-inflammatory Effect Of Nicotine On Ibdmentioning
confidence: 75%
“…Some diseases, such as obesity, fatty liver, and inflammatory bowel disease, are associated with their imbalance. [4][5][6] Recently, growing evidence has shown that changes in the intestinal flora play an important role in the pathogenesis of liver disease; however, the conclusions of various studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, in a following work where HT29‐MTX cells were added to the model, ongoing inflammation did not affect the inflammatory response. [ 94 ] Marescotti and co‐workers [ 98 ] also established a model of the inflamed mucosa combining Caco‐2 and HT29‐MTX with THP‐1‐differentiated macrophages and observed a decrease in TEER and an increase in intestinal permeability and cytokine release. The authors claimed the model was suitable to assess the anti‐inflammatory properties of compounds after pre‐treating the cells with budesonide and TPCA‐1 and confirming the prevention of LPS‐induced inflammation.…”
Section: In Vitro Models Of Gut Inflammationmentioning
confidence: 99%